Strategi Komunikasi Pemasaran melalui Digital Marketing Institut Sains dan Teknologi Terpadu Surabaya - Candra Gunawan, Ardalina Luvitasari; Harliantara, Harliantara (Universitas Islam Balitar, 2023)
Institut Sains dan Teknologi Terpadu Surabaya (ISTTS) is experiencing a decreasing trend in the number of students from the 2021/2021, 2021/2022, and 2022/2023 periods. This research uses Integrated Marketing Communication (IMC) theory, Digital Marketing, and Marketing Public Relation strategies as a basis to analyze data collected through evaluative descriptive discourse analysis of digital promotional materials used by ISTTS. Based on the results of the study, it can be concluded that the digital marketing communication strategy and public relation strategy implemented by ISTTS in their student admission activities are effective in increasing the number of student applicants and improving their institutional image. This research contributes to the development of integrated marketing communication theory and provides recommendations for other educational institutions in developing their digital marketing communication and public relation strategies.